India Hypertension Control Initiative—Hypertension treatment and blood pressure control in a cohort in 24 sentinel site clinics - Prabhdeep Kaur; Abhishek Kunwar; Meenakshi Sharma; Jhilam Mitra; Chinmoyee Das; Leimapokpam Swasticharan; Tapas Chakma; Sampada Dipak Bangar; Vettrichelvan Venkatasamy; Raviteja Dharamsoth; Saurabh Purohit; Sadhana Tayade; et al. (The Journal of Clinical Hypertension, 2021)
Abstract The India Hypertension Control Initiative (IHCI) is a multi‐partner initiative, implementing and scaling up a public health hypertension control program across India. A cohort of 21,895 adult hypertension patients in 24 IHCI sentinel site facilities in four Indian states (Punjab, Madhya Pradesh, Maharashtra, and Telangana), registered from January 2018 until June 2019 were assessed at baseline and then followed up for blood pressure (BP) control and antihypertensive medication use. Among all registrations, 11 274 (51%) of the patients returned for a follow‐up visit between July 2019 and September 2019. Among patients returning for follow‐up, 26.3% had BP controlled at registration, and 59.8% had BP controlled at follow‐up (p < .001). The absolute improvement in BP control was more than two times greater in primary care (48.1 percentage point increase) than secondary care facilities (22.9 percentage point increase). Most IHCI patients received prescriptions according to state‐specific treatment protocols. This study demonstrates that a scalable public health hypertension control program can yield substantial BP control improvements, especially in primary care settings. However, high loss to follow‐up limits population health impact; future efforts should focus on improving systems to increase the likelihood that patients will return to the clinic for routine hypertension care.